Pembuatan Kolase Gambar dari Sampah Plastik sebagai Pemanfaatan Limbah dalam Upaya Menjaga Lingkungan di Panti Asuhan Tunas Bangsa, Labuhan Batu - Dedek Andriani; Indana Zulfa; Sarinah D. Silalahi (International Forum of Researchers and Lecturers, 2025)
Plastic has become an inseparable part of human life today. Various products used by humans in their daily lives are often found to come from plastic. The use of plastic is growing and its utilization is increasingly widespread in the field of life so that if this waste is not managed properly it will cause pollution. Therefore, this program aims to empower children at the Tunas Bangsa Orphanage, Labuhan Batu by teaching collage skills in utilizing plastic waste into a picture collage. In addition, this program also aims to introduce recycling of plastic waste by being able to select and sort waste in the surrounding environment. This training is equipped with the values ​​of Pancasila and Citizenship Education (PPKn) such as increasing awareness of the rights and obligations of each individual to feel comfortable in the environment and maintain environmental cleanliness. It is hoped that through this program, children can develop creativity skills and play an active role in maintaining environmental cleanliness away from plastic waste. This program also opens up opportunities for them to contribute to the movement to maintain environmental sustainability far from waste.